Use of organic precursors and graphenes in the controlled synthesis of carbon-containing nanomaterials for energy storage and conversion - Yang, Shubin; Bachman, Robert E.; Feng, Xinliang; Muellen, Klaus (Accounts of Chemical Research, 2013)
The development of high-performance electrochemical energy storage and conversion devices, including supercapacitors, lithium-ion batteries, and fuel cells, is an important step on the road to alternative energy technologies. Carbon-containing nanomaterials (CCNMs), defined here as pure carbon materials and carbon/metal (oxide, hydroxide) hybrids with structural features on the nanometer scale, show potential application in such devices. Because of their pronounced electrochemical activity, high chemical and thermal stability and low cost, researchers areinterested in CCNMs to serve as electrodes in energy-related devices.Various all-carbon materials are candidates for electrochemical energy storage and conversion devices. Furthermore, carbon-based hybrid materials, which consist of a carbon component with metal oxide- or metal hydroxide-based nanostructures, offer the opportunity to combine the attractive properties of these two components and tune the behavior of the resulting materials. As such, the design and synthesis of CCNMs provide an attractive route for the construction of high-performance electrode materials. Studies in these areas have revealed that both the composition and the fabrication protocol employed in preparing CCNMs influence the morphology and microstructure of the resulting material and its electrochemical performance. Consequently, researchers have developed several synthesis strategies, including hard-templated, soft-templated, and template-free synthesis of CCNMs.In this Account, we focus on recent advances in the controlled synthesis of such CCNMs and the potential of the resulting materials for energy storage or conversion applications. The Account is divided into four major categories based on the carbon precursor employed in the synthesis: low molecular weight organic or organometallic molecules, hyperbranched or cross-linked polymers consisting of aromatic subunits, self-assembling discotic molecules, and graphenes. In each case, we highlight representative examples of CCNMs with both new nanostructures and electrochemical performance suitable for energy storage or conversion applications. In addition, this Account provides an overall perspective on the current state of efforts aimed at the controlled synthesis of CCNMs and identifies some of the remaining challenges. © 2012 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20